(untitled) (Burbank, CA., 1998)
Robin Williams portrays English professor John Keating, who, in an age of crew cuts, sport coats and cheerless conformity, inspires his students to live life to the fullest, exclaiming "Carpe Diem, lads! Seize the day. Make your lives extraordinary!" The charismatic teacher's emotionally charged challenge is met by his students with irrepressible enthusiasm--changing their lives forever.
Keywords: Trường trung học,High schools; Kịch,Drama; Hoa Kỳ,United States